Pendidikan Orang Tua terhadap Kemampuan Literasi Membaca pada Anak Usia Dini di Masa Pandemi (PIAUD IAIN Kudus, 2021)
Children’s learning while at home requires guidance from parents. One of them is in the use of gadgets and parental knowledge as the main factor in developing children’s literacy skills. The ability of children’s literacy is the ability to read. The purpose of this study is to determine the effect of parental education on children’s reading literacy skills during pandemics. The method used in this study is quantitative method. The data were collected by using questionnaire, observation, and interviews. The results of the study are that parental education has an influence on early childhood reading literacy skills in pandemic times. Parental education plays a role in helping children in learning, especially in improving children’s reading skills. Learning can be applied through storytelling activities.